Reimagining Drug Potential: Machine Learning As A Catalyst In Drug Repurposing - Sanap Mayuri P,; Prof. B.T. Jagtap, (Asian Journal of Pharmaceutical Research and Development, 2025)
Drug discovery has long been a cornerstone of medical progress, yet the conventional path of developing new therapeutics is notoriously lengthy, costly, and fraught with uncertainty. On average, it requires more than a decade of intensive research, billions of dollars in investment, and multiple phases of preclinical and clinical testing to bring a single novel drug to market. Despite such efforts, the attrition rate remains strikingly high, with only a small fraction of candidates achieving regulatory approval. In this context, drug repurposing, also known as drug repositioning, has emerged as a pragmatic and highly valuable strategy to address unmet medical needs and optimise available therapeutic resources. The history of drug repurposing is deeply embedded in the evolution of modern pharmacology. Early examples demonstrate how serendipitous observations, clinical experiences, and detailed pharmacological studies gave new life to compounds originally designed for unrelated purposes. Aspirin, first introduced as an analgesic and antipyretic, was later recognised for its antiplatelet effects, transforming it into a cornerstone therapy for cardiovascular diseases. Thalidomide, infamous for its teratogenic effects, was subsequently repurposed as an immunomodulatory drug to treat multiple myeloma and leprosy-related complications. Sildenafil, initially developed for angina, gained global recognition when repurposed for erectile dysfunction and later for pulmonary arterial hypertension. Keywords: Drug discovery has long been a cornerstone of medical progress, yet the conventional path of developing new therapeutics is notoriously lengthy, costly, and fraught with uncertainty. On average, it requires more than a decade of intensive research, billions of dollars in investment, and multiple phases of preclinical and clinical testing to bring a single novel drug to market. Despite such efforts, the attrition rate remains strikingly high, with only a small fraction of candidates achieving regulatory approval. In this context, drug repurposing, also known as drug repositioning, has emerged as a pragmatic and highly valuable strategy to address unmet medical needs and optimise available therapeutic resources. The history of drug repurposing is deeply embedded in the evolution of modern pharmacology. Early examples demonstrate how serendipitous observations, clinical experiences, and detailed pharmacological studies gave new life to compounds originally designed for unrelated purposes. Aspirin, first introduced as an analgesic and antipyretic, was later recognised for its antiplatelet effects, transforming it into a cornerstone therapy for cardiovascular diseases. Thalidomide, infamous for its teratogenic effects, was subsequently repurposed as an immunomodulatory drug to treat multiple myeloma and leprosy-related complications. Sildenafil, initially developed for angina, gained global recognition when repurposed for erectile dysfunction and later for pulmonary arterial hypertension.